The Prism Look at the Rhetoric of Apologia: Lessons from the Apologetic Speeches of Tiger Woods and Chris Brown - Desideria Murti (Jurnal InterAct, 2013)
This article is a rhetorical criticism of two apologetic speeches from two celebrities. Chris Brown and Tiger Woods articulated their apology to public through visual media during crisis situation. To restore their image, avoid lawsuits, and stabilize trust to their apologetic stakeholders, their speeches were codified under visual composition, structure of speeches, offense identification, and the moment of silence. I used Black’s prism analysis to criticize the complexity of apologetic address of celebrity. Result, rhetoric of apologia exercised a negotiation process of identity and it indicated the authenticity of the speakers,   avoidance of   interruption,   prevention of ambivalence, engraving the audience emotion, and sustaining their personal objectives. The article concluded by answering what kind of various constellation tactics in saying “sorry.”